ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL ALJABAR DITINJAU DARI KEMAMPUAN BERPIKIR LOGIS - Rohim, Abdur; Prayogi, Budi Teguh (INSPIRAMATIKA, 2023)
One of the important branches of mathematics, often considered difficult and abstract is algebraic material. The introduction of algebraic concepts needs to be given to students, because these concepts can be used as students' capital to study further learning material. If from the start students have difficulty understanding algebraic concepts, then this can also affect student learning outcomes in the future. The purpose of this study was to describe students' difficulties in solving problems related to algebra in terms of their ability to think logically and to analyze the factors that cause students' difficulties. This study uses a qualitative descriptive research method. This study used test and interview data collection methods. To analyze the data, researchers used data reduction models, data representation, and drawing conclusions. The results showed that students with very low abilities did not fulfill all indicators of logical thinking. Students with sufficient abilities are able to fulfill 4 indicators in addition to the concluding indicator. Very high ability students are able to fulfill all indicators of logical thinking. The factors that lead to difficulties in solving algebra problems are lack of motivation, lack of interest in learning algebra, lack of understanding of questions, and accuracy in translating mathematical symbols.